Challenges Toward Learning Mathematics - Pokhrel, Maheshwor (Shikshya Sandesh, 2023)
Mathematics is the science of all sciences and the art of all arts. Mathematicians had been concerned with everyday problems. However, today’s students are uninterested in learning mathematics. My research is based on narrative inquiry and the interpritivism philosophy paradigm. The main objective of this research is to identify students’ challenges to learning mathematics. I gathered information from eight participants from two schools, one public and one private. To achieve the research objective, in-depth interviews were conducted with research participants. I had narrated views about perception and challenges towards learning mathematics from my participants. After analysis and interpretation of data, challenges towards learning mathematics were mathematic anxiety, lack of interest, negative perceptions, lack of students labor, present practice of teaching and unqualified and nonprofessional teachers, traditional teaching methods with rote learning, lack of parents awareness, low socio-economic status of parents, low self-efficacy, lack of motivation and counseling, low self-efficacy of students, unpractical curriculum and courses, poor school administration and physical facilities, math myth. Public school students and non-optional mathematics students had faced more challenges than private school students and optional mathematic students.